2022
DOI: 10.1371/journal.pone.0276111
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processing Therapy or Relapse Prevention for comorbid Posttraumatic Stress Disorder and Alcohol Use Disorder: A randomized clinical trial

Abstract: Objective To compare a Posttraumatic Stress Disorder (PTSD) treatment (Cognitive Processing Therapy; CPT), an Alcohol Use Disorder (AUD) treatment (Relapse Prevention; RP), and assessment-only (AO) for those meeting diagnostic criteria for both PTSD and AUD. Method Participants with current PTSD/AUD (N = 101; mean age = 42.10; 56% female) were initially randomized to CPT, RP, or AO and assessed post-treatment or 6-weeks post-randomization (AO). AO participants were then re-randomized to CPT or RP. Follow-ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“…Indeed, previous research has shown that emotion regulation change coincides with a treatment-related change in PTSD (Jerud et al, 2016), likely due to the fact that the use of maladaptive emotion regulation strategies is associated with PTSD symptom severity (Boden et al, 2013; Ehring & Quack, 2010; Tull et al, 2007). Additionally, treatments targeting alcohol use can lead to reductions in co-occurring PTSD (Simpson et al, 2020). More research is needed to understand the sequence of symptom change and whether there are advantages to targeting emotion regulation and drinking for downstream improvements in other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research has shown that emotion regulation change coincides with a treatment-related change in PTSD (Jerud et al, 2016), likely due to the fact that the use of maladaptive emotion regulation strategies is associated with PTSD symptom severity (Boden et al, 2013; Ehring & Quack, 2010; Tull et al, 2007). Additionally, treatments targeting alcohol use can lead to reductions in co-occurring PTSD (Simpson et al, 2020). More research is needed to understand the sequence of symptom change and whether there are advantages to targeting emotion regulation and drinking for downstream improvements in other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Using R statistical software, 1,000 data sets were generated based on the linear mixed models described below. Estimates for model parameters for standardized PTSD scores (e.g., baseline intercept, slopes for time, distribution of random effects) were guided by preliminary data from a prior trial (Simpson et al, 2022). We specified missingness of 13% and 19% at 3- and 6-month follow-ups, respectively, according to missing data patterns in similar studies (Walker et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For example, COPE (Concurrent Treatment of PTSD and Substance Use Disorders Using Prolonged Exposure) [25] and Seeking Safety [26] are effective integrated treatments for addressing traumatic stress and alcohol misuse simultaneously. In addition, traumatic stress treatment alone (ie, Cognitive Processing Therapy) has been shown to reduce alcohol and other substance use among survivors of SA [27]. Finally, a psychoeducational video shown to survivors of recent SA during a forensic examination was found to be an effective early intervention to reduce the risk of alcohol misuse among recent survivors with a previous history of exposure to SA [28].…”
Section: Mental Health Service Use For Traumatic Stress and Alcohol M...mentioning
confidence: 99%